Wake Forest student dormitory room with centerfolds - (:unkn) unknown (Z. Smith Reynolds Library, 1960)
nd
Male students in residence hall room, with centerfolds and Playboy logo on wall in background.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth